A Bibliometric Analysis of Marine Tourism - Indra Ratna Sari; Jufidah (JURNAL AKADEMISI VOKASI, 2025)
This study is motivated by the many phenomena that occur in marine tourism. Starting from protected marine areas, plastic waste that pollutes the marine environment, and other phenomena caused by marine tourism. Many studies that examine this phenomenon cultivate motivation to study all phenomena that exist in marine tourism. The purpose of this study is to determine research trends related to marine tourism using bibliometric analysis as a research method. The data was obtained through Scopus with the initial data amount of 1237 to 978 documents after going through the filtering process. The document is downloaded via the RIS file and matrix analysis is performed using Publish or Perish. Data mapping uses Vos Viewer software which is divided into four parts, namely Network Visualization, Overlay Visualization, Density Visualization, and author relationships based on Overlay Visualization. The results show that based on publication statistics, 2021 has the highest total publications with a total of 230 documents. The most types of documents are articles with a total of 671 documents and the type of source comes from journals with a total of 750 documents. Vos Viewer mapping shows that research trends regarding marine tourism include "Tourism", "Sustainable Development", "Climate Change", "Coral Reef", "Ecotourism", "Marine Protected Area", and "Tourism Management". Keywords: Bibliometric Analysis; Publish or Perish; Marine Tourism; Vos Viewer